Distribuição e incremento do fósforo em latossolo sob três modos de aplicação do fertilizante fosfatado em soja e milho - Tres, Gessika (2017)
Phosphorus is considered an essential element in the development of plants, presenting low mobility in the soil, but in the plant is mobile in the phloem. One of the factors that changes the dynamics of phosphorus in the soil is its absorption by the crop, and the mode of application. The objective of this work was to evaluate the distribution of P in the soil and its increment, besides evaluating the soybean and corn crops, in three ways of application. The design was a randomized block design with sub-subdivided plots in the space (first factor, modes of application of phosphate fertilizer, second factor, in-line and in between-line position, and third factor, depth), with 7 replicates. The soil under study is a Dark-Red Latosol, with a low content of P. The summer soybean and summer corn cultures were evaluated in succession of cultures, in no-tillage system, with a formulation containing monomeric phosphate (MAP) and monocalcium phosphate (SSP). Were evaluated the nutritional status (g kg-1 de P), dry shoot biomass (kg ha-1 de MS), shoot extraction and export of P (kg ha- 1 de P), height of plants (m), mass of one thousand grains (gramas) and productivity (kg ha-1) in summer soybean and corn crops. For the soil, the analyzes were performed at 11 sampling points, 3 lines and 8 lines between 4 depths (0-0,05; 0,05-0,10; 0,1- 0,15; 0,15-0,20 m) before sowing of soybean and after harvesting of corn. In the soil with low P content, the mode of application of the phosphate fertilizer in broadcast surface can be handled for the culture of soybean, and the culture of corn, the best response was obtained on application in furrow. The results obtained in the soil showed that the mode of application parceled increased P content in a large part of the sampled profile. When only the broadcast in te surface, these were positioned in greater proportion on the surface. When in along the sowing furrow, there were increases mainly in the place of deposition of the phosphate fertilizer. For all modes of application there were increments in points in the lines and between the lines. Possibly there was influence of the roots in the increase of the P content in the soil profile.